Analysis of centrifugal deliquoring with cylindrical filter medium - Fujiwara, Ryoko; Iwasaki, Tomohiro; Jami, Mohammed Saedi; Iwata, Masashi (2018)
Cylindrical filter medium whose surface is parallel to the centrifugal force plays an important role in the improvement of the centrifugal deliquoring rate of a difficult-to-filter material. The mechanism of centrifugal deliquoring with the cylindrical medium is discussed by using a soy sauce mash as experimental material. The use of the cylindrical medium accelerates the deliqouring process and mitigates the negative effect of sample thickness on the deliquoring time.